Macular thickness in healthy Libyan adults measured by optical coherence tomography - Bukhatwa, Samar; Eldressi, Sabah; Elzlitni, Naeima (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Objectives: Management of various macular diseases depends on macular thickness which is measured quantitatively by optical coherence tomography. Studies have reported variations in the macular thickness by race and gender. The aim of this study was to determine the normal macular thickness measurements in healthy eyes of Libyans. Subjects and Methods: This study was conducted at the Ophthalmology Outpatient Department at Alkeish polyclinic in the period between January and December 2018. This study included 243 healthy eyes of 131 Libyan adults of both genders who underwent a complete ophthalmic examination including spectral domain optical coherence tomography to measure the macular thickness at the nine areas corresponding to Early Treatment Diabetes Retinopathy Study map (ETDRS). Results: The mean age of the study population was 48.3 ± 16.6 years (ranged between 21 and 79 years), the thickness in the foveola/center point of macula (CPT) was 192 ± 22.4 μm, the central foveal thickness was 230.3 ± 18.3 μm, and the average thickness was 270.1 ± 9.4 μm. Males were having more thickness than females. Conclusions: Foveola's thickness (CPT) in Libyan adults measured by spectral domain optical coherence tomography is thinner than that of previously published studies. Moreover, the central foveal thickness is less than that of many other studies and males have more thickness than females in all the areas of ETDRS map, which indicates that gender must be taken into consideration while interpreting macular retinal thickness data.
Keywords: Libya; normal macular thickness; optical coherence tomography; spectral domain